Oil-Producing Metabolons Containing DGAT1 Use Separate Substrate Pools from those Containing DGAT2 or PDAT. Issue 2 (30th July 2020) - Regmi, Anushobha; Shockey, Jay; Kotapati, Hari Kiran; Bates, Philip D.
Abstract: Diacylglycerol pools are differentially used by various classes of triacylglycerol-producing acyltransferases, which affects the path of carbon flux into seed oil, and its composition. Abstract: Seed triacylglycerol (TAG) biosynthesis involves a metabolic network containing multiple different diacylglycerol (DAG) and acyl donor substrate pools. This network of pathways overlaps with those for essential membrane lipid synthesis and utilizes multiple different classes of TAG biosynthetic enzymes. Acyl flux through this network ultimately dictates the final oil fatty acid composition. Most strategies to alter seed oil composition involve the overexpression of lipid biosynthetic enzymes, but how these enzymes are assembled into metabolons and which substrate pools are used by each is still not well understood. To understand the roles of different classes of TAG biosynthetic acyltransferases in seed oil biosynthesis, we utilized the Arabidopsis ( Arabidopsis thaliana ) diacylglycerol acyltransferase mutant dgat1-1 (in which phosphatidylcholine:diacylglycerol acyltransferase (AtPDAT1) is the major TAG biosynthetic enzyme), and enhanced TAG biosynthesis by expression of Arabidopsis acyltransferases AtDGAT1 and AtDGAT2, as well as the DGAT2 enzymes from soybean ( Glycine max ), and castor ( Ricinus communis ), followed by isotopic tracing of glycerol flux through the lipid metabolic network in developing seeds. The results indicate each acyltransferase has a unique effect on seed oil composition. AtDGAT1 produces TAG from a rapidly produced phosphatidylcholine-derived DAG pool. However, AtPDAT1 and plant DGAT2 enzymes utilize a different and larger bulk phosphatidylcholine-derived DAG pool that is more slowly turned over for TAG biosynthesis. Based on metabolic fluxes and protein:protein interactions, our model of TAG synthesis suggests that substrate channeling to select enzymes and spatial separation of different acyltransferases into separate metabolons affect efficient TAG production and oil fatty acid composition.